Using pictures in teaching vocabulary of English to the second year students of Mechanical Department at Haiphong Industrial Vocational College = Sử dụng tranh ảnh trong dạy từ vựng tiếng Anh cho sinh viên năm thứ hai Khoa Cơ khí trường Cao đẳng nghề Công nghiệp Hải Phòng. M.A Thesis Linguistics: 60 14 10 - Nguyễn, Thị Thu Hòa (2017)
The study applied both qualitative and quantitative a pproaches with two methods of data collection: survey and observation. The quantitative data were collected from questionnaires and were analyzed statistically, while the qualitative data were collected from the class observation. Survey questionnaires were used to collect information and evidence for study with the hope that the research would be reliable. Class observation was carried out to supplement the survey questionnaires. It is hope the combination of the two methods would make the data more valid and reliable